2020
DOI: 10.1177/2474126420972878
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year Follow-up of Microincisional Vitrectomy Surgery, Endolaser Tumor Ablation, and Gene-Expression Profiling in Small Uveal Melanoma

Abstract: Purpose: This work evaluates a microincisional vitrectomy surgical (MIVS) approach to endolaser ablation of small uveal malignant melanoma by incorporating genetic tumor classification as a means to avoid radiotherapy while maintaining local tumor control without compromising visual acuity (VA). Methods: An institutional review board–approved, single-surgeon, retrospective analysis was conducted of a consecutive case series of all patients with tumors less than 2.5 mm in apical thickness who underwent MIVS, en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“… 48 Murray et al retrospectively evaluated a case series of small UM undergoing early fine-needle aspiration biopsy combined with pars plana vitrectomy and endolaser ablation. 47 The study found no patients developed metastasis in the follow up period, suggesting that early treatment may lower the risk of mortality compared to observation alone.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“… 48 Murray et al retrospectively evaluated a case series of small UM undergoing early fine-needle aspiration biopsy combined with pars plana vitrectomy and endolaser ablation. 47 The study found no patients developed metastasis in the follow up period, suggesting that early treatment may lower the risk of mortality compared to observation alone.…”
Section: Discussionmentioning
confidence: 78%
“… 45 , 46 Despite the availability of effective treatments for the primary tumor, more than 50% of UM patients develop metastatic disease suggesting that UM may metastasize prior to the time of treatment. 45 , 47 Consequently, there is a need for identifying and treating small UM to minimize the number of melanocytic choroidal tumors that are observed and subsequently grow during the observation period. The importance of treating small UM was additionally emphasized by Eskelin et al, who measured doubling time in both untreated and treated metastatic UM and proposed that most metastases begin up to 5 years prior to primary tumor treatment.…”
Section: Discussionmentioning
confidence: 99%
“…6 Combined pars plana vitrectomy with endolaser treatment has also shown to be an efficient method to treat these small melanomas, with a recurrence rate of only 1.7%. 7 Medium-sized tumors (<10 mm in apical height and <15 mm in basal diameter) are treated with radiation therapy and plaque brachytherapy using iodine-125. 4 Plaque radiotherapy can be custom designed to treat any tumor size up to 12 mm in thickness.…”
Section: Discussionmentioning
confidence: 99%
“…It is most often used in addition with plaque radiotherapy 6 . Combined pars plana vitrectomy with endolaser treatment has also shown to be an efficient method to treat these small melanomas, with a recurrence rate of only 1.7% 7 …”
Section: Discussionmentioning
confidence: 99%